PENGEMBANGAN APLIKASI ANDROID INTERAKTIF BERBASIS MULTIPEL REPRESENTASI PADA MATERI STRUKTUR ATOM SEBAGAI SUMBER BELAJAR MANDIRI SISWA DI SMA KATOLIK KARITAS TOMOHON - Lahimade, Susye Frigawati; Rumondor, Desire A. S; Palilingan, Septiany Ch (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to test the feasibility of multiple representation-based interactive Android applications on atomic structure material as an independent learning resource for students at Karitas Tomohon Catholic High School. The research method used is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results showed that this application was able to facilitate learning by integrating three levels of chemical representation (macroscopic, microscopic, and symbolic). The research subjects included chemistry teachers, grade X students, especially grade X-A, as well as two media experts and two material experts. Validation by media experts showed a feasibility level of 87%, while material expert validation reached 96%. The chemistry teacher's response gave a feasibility level of 100%, while the student's response reached 88%, both of which were included in the very feasible category. This application is expected to be an innovation in chemistry learning, especially as an interesting and useful independent learning media.